Digital Transformation Readiness and Its Impact on Achieving Sustainability Goals of Public Sector Organizations in Indonesia - Shinta Happy Yustiari; Yaen Miftakhul Laily; I Gede Eko Putra Sri Sentanu; Fijri Adzanura Zikri (Universitas Kadiri, 2026)
Digital transformation serves as a pivotal driver in advancing the Sustainable Development Goals (SDGs), particularly within the public sector. This research evaluates how the digital readiness of public organizations in Indonesia influences their capacity to achieve long-term sustainability. Using a qualitaive methodology, this study integrates literature reviews, policy document analysis, and performance reports with direct observations of operational activities across various central and regional government agencies. The findings suggest that digital transformation in the public sector is heavily contingent upon internal systems, organizational culture, and leadership support. Utimately, elevating an organization’s digital maturity is essential for the formulation of resilient policies and the delivery of sustainable public services in the digital age.